The Pencak Silat College in Developing National Character: Paguron Pencak Silat Dalam Menumbuhkan Karakter Bangsa - Aprillio Poppy Belladonna; Rama Adha Septiana (Journal of Physical and Outdoor Education, 2022)
The purpose of this study was to find out and understand the Paguron Pencak Silat in growing the nation's character. The method used is descriptive analysis with a qualitative approach. The conclusion from the results of the research is that the Paguron Pencak Silat Gagak Lumayung can grow the character of the Nation such as (1) religious values, namely when starting pencak silat practice always pray first, even when you have learned pencak silat, end with a prayer together. (2) the value of discipline through (a) being present on time in practice, (b) in memorizing movements, discipline also appears because if there is no discipline, pencak silat students will not be able to memorize all the movements taught. (3) the value of hard work can grow through pencak silat because in practice each student must work hard in memorizing pencaksilat movements and when they will follow pairs of giri then hard work in practicing is very supportive for their success in participating in competitions. (4) the value of honesty, namely admitting mistakes for evaluation in the next exercise so that it is even better. Sportsmanship in the race is also part of honesty. (5) the value of responsibility, namely the pencak silat student is responsible for every word and deed